Exploring the impact of cooking techniques and storage conditions on resistant starch levels in mung beans and its effect upon blood glucose level and lipid profile in vivo - Chauhan, Saloni; Kaur, Harpreet; Aggarwal, Renuka; Kaur, Prabhjot; Bains, Kiran (Frontiers in Nutrition, 2024)
Introduction Mung beans contain various antinutritional components. Processing and cooking methods can reduce these antinutritional factors and increase the availability and digestibility of nutrients. Resistant starch is also known as dietary fiber, which helps to reduce the cholesterol and glucose level in blood. It is formed during cooking and storage of food at low temperature. Objectives This study aimed to assess the effects of cooking and storage temperature on the formation of resistant starch in processed mung bean, as well as its effect on blood glucose levels and lipid profile in humans and rats. Methods The common cooking methods namely boiling, steaming after germination, roasting, and pressure cooking were chosen. The cooked samples were stored at different temperatures including freshly prepared within 1 h (T1), stored for 24 h at room temperature (20–22°C) (T2), kept at 4°C for 24 h (T3), and reheated after storing at 4°C for 24 h (T4). Results The study revealed that germinated-steamed mung beans had significantly higher levels of resistant starch (27.63 ± 0.76), and lower level of glycemic index (26.28 ± 3.08) and amylose (40.91 ± 0.06) when stored at 4°C for 24 h (T3) followed by (T2), (T4), and (T1) as compared to other cooking methods (boiling, pressure cooking, and roasting). The germinated-steamed mung beans (T1) resulted in 96% decline in blood glucose parameters of rats (36 Wistar albino rats aged 2 to 3 months were selected) than the control group as observed in 28 days diet intervention (100 mg/kg resistant starch orally). Conclusion There is a need to make people aware about the selection of appropriate cooking (steamed after germination) and storage methods (T3) to increase the RS content and to lower the glycemic index of food at domestic level.